Composite material regenerated from waste and preparation method thereof
By combining chitosan powder with non-metallic powder from waste printed circuit boards and using silane coupling agents to improve compatibility, a composite material with mechanical properties was prepared. This solved the problem of the difficulty in degrading waste polypropylene plastics and printed circuit boards, and realized the recycling of resources and environmental protection.
Patent Information
- Application Number
- CN202511279796.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-09
- Publication Date
- 2025-12-12
AI Technical Summary
Waste polypropylene plastics and waste printed circuit boards are difficult to degrade, causing environmental pollution, and existing technologies have failed to effectively utilize them as resources.
Chitosan powder was mixed with non-metallic powder from waste printed circuit boards, and then surface-treated and initially cross-linked with a silane coupling agent. Subsequently, it was mixed with waste polypropylene particles, and the composite material was prepared by extrusion granulation and injection molding.
The prepared composite material possesses certain mechanical properties, effectively saves resources, reduces costs, reduces environmental pollution, and improves the recycling rate of waste.
Smart Images

Figure CN121108626A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of environment-friendly composite materials, and particularly relates to a composite material regenerated from waste and a preparation method thereof. BACKGROUND
[0002] The stock of industrial waste such as waste polypropylene plastic and waste printed circuit board in China is extremely large. Taking polypropylene as an example, it accounts for 20%-30% of the volume of municipal solid waste, and about 90% of it is filled or directly discarded in the natural environment. Since polypropylene is extremely difficult to degrade, it will exist in the environment for a long time, and during the process of fragmentation or aging, it will release microplastics. The pollution of microplastics in the atmosphere, water body and soil will migrate and form superimposed pollution effects, causing serious and lasting harm to the ecological environment.
[0003] On the other hand, waste printed circuit boards are core components in various electronic products and modern equipment, and their content in commonly used household appliances can be as high as 10wt%. The non-metallic part of this kind of waste is mainly composed of epoxy resin and glass fiber. Since the chemical properties of epoxy resin and glass fiber are relatively stable, they are extremely difficult to degrade in the natural environment. If they are not effectively recycled and discarded at will, they will also cause serious pollution to the ecological environment. SUMMARY
[0004] Therefore, in view of the above problems, it is necessary to provide a composite material regenerated from waste and a preparation method thereof, so as to effectively save resources, reduce costs, and reduce the pollution of the above waste to the environment by recycling and utilizing waste polypropylene plastic and the non-metallic part of waste printed circuit board to prepare a composite material with certain mechanical properties.
[0005] In one aspect, the present application provides a preparation method of a composite material regenerated from waste, comprising the following steps: Step 1: mixing and stirring chitosan powder and waste printed circuit board non-metallic powder according to a mass ratio of (15-20):(30-60) to obtain a treated mixed powder; Step 2: adding a certain amount of hydrolyzed silane coupling agent into the treated mixed powder under a predetermined temperature for stirring, so as to perform surface treatment and preliminary cross-linking on the treated mixed powder by the silane coupling agent, and obtaining a modified powder, wherein the mass ratio of the silane coupling agent to the treated mixed powder is (1.4-1.6):100; Step 3: mixing and stirring the modified powder, waste polypropylene particles and antioxidant according to a mass ratio of (30-50):200:0.5 to obtain a composite sample powder; Step 4: The composite sample powder is extrusion granulation and injection molding to make a composite material regenerated by waste.
[0006] Preferably, in the step 1, the chitosan powder is obtained by the following steps: S11: Put the waste shrimp and crab shells into a container, add 1mol / L-2mol / L sodium hydroxide solution to submerge the waste shrimp and crab shells, then heat the sodium hydroxide solution to boiling for 1h-2h, and then filter to obtain the extracted shrimp and crab shells; S12: Soak the extracted shrimp and crab shells in 0.9mol / L-1.1mol / L hydrochloric acid at room temperature for 4h-8h, then filter and crush to obtain chitin powder of a certain particle size, wherein the mass ratio of the hydrochloric acid to the extracted shrimp and crab shells is 1:(5-10), and the particle size of the chitin powder is 80-100 mesh; S13: Dissolve the chitin powder in an industrial sodium hydroxide solution with a mass fraction of 40%-50% to obtain a mixed solution, wherein the mass ratio of the chitin powder to the industrial sodium hydroxide solution is (1-2):(10-20); S14: Heat the mixed solution to a temperature of 60℃-80℃ for 6h-12h, and then filter to obtain the treated chitosan powder; S15: Wash the treated chitosan powder with distilled water to neutralize it, and then dry it at a temperature of 55℃-65℃ to obtain the chitosan powder.
[0007] Preferably, in the step 1, the specific steps for obtaining the waste printed circuit board non-metallic powder are: crushing the non-metallic part of the waste printed circuit board and then sieving to obtain the waste printed circuit board non-metallic powder with a particle size of 80-100 mesh.
[0008] Preferably, the step 1 is specifically: placing the chitosan powder and the waste printed circuit board non-metallic powder into a high-speed mixer for stirring, and then obtaining the treated mixed powder, wherein the mass ratio of the chitosan powder to the waste printed circuit board non-metallic powder is (15-20):(30-60).
[0009] Preferably, the step 2 is specifically: after the temperature in the high-speed mixer rises to the predetermined temperature, a certain amount of hydrolyzed silane coupling agent is added to the treated mixed powder in multiple times and continuously stirred for 15min-25min to perform surface treatment and preliminary cross-linking on the treated mixed powder by the silane coupling agent, and then a modified powder is obtained, wherein the predetermined temperature is 75℃-85℃, and the mass ratio of the silane coupling agent to the treated mixed powder is (1.4-1.6):100.
[0010] Preferably, the step 2 is followed by a drying step, which is specifically: placing the modified powder into an electric heating constant temperature drying oven, drying at 75-85℃ for 2.5-3.5h to remove excess moisture.
[0011] Preferably, the step 3 is further added with maleic anhydride grafted polypropylene as a compatibilizer of the composite sample powder, wherein the mass ratio of the modified powder, the waste polypropylene powder, the antioxidant and the maleic anhydride grafted polypropylene is (30-50):200:0.5:(6-9).
[0012] Preferably, the step 3 is further added with OBC elastomer as a toughening agent of the composite sample powder, wherein the mass ratio of the modified powder, the waste polypropylene powder, the antioxidant and the OBC elastomer is (30-50):100:0.5:(9-15).
[0013] Preferably, the step 3 is further added with a β nucleating agent as an induced nucleating agent of the composite sample powder, wherein the mass ratio of the modified powder, the waste polypropylene powder, the antioxidant and the β nucleating agent is (30-50):100:0.5:(1-2).
[0014] In another aspect, the present application provides a composite material regenerated from waste, which is prepared by the method for preparing a composite material regenerated from waste according to the above aspect.
[0015] According to the above technical solution, the present application provides a method for preparing a composite material regenerated from waste, which first mixes and stirs chitosan powder and waste printed circuit board non-metal powder according to a mass ratio of (15-20):(30-60) to obtain a to-be-treated mixed powder; then adds a certain amount of hydrolyzed silane coupling agent into the to-be-treated mixed powder at a predetermined temperature to stir, so as to perform surface treatment and preliminary cross-linking on the to-be-treated mixed powder by the silane coupling agent, and obtain a modified powder, wherein the mass ratio of the silane coupling agent to the to-be-treated mixed powder is (1.4-1.6):100; subsequently, the modified powder, waste polypropylene particles and an antioxidant are mixed and stirred according to a mass ratio of (30-50):200:0.5 to obtain a composite sample powder; finally, the composite sample powder is extruded and granulated and injection molded to prepare a composite material regenerated from waste, and through mechanical property testing, the tensile strength of the composite material prepared by the above method can reach 34.12MPa, the bending strength can reach 35.10MPa, and the impact strength can reach 24.34kJ / m 2 .
[0016] The present application has the beneficial effects compared with the prior art: the present application firstly modifies the chitosan powder and the non-metallic powder of the waste printed circuit board, specifically, the silanol group of the silane coupling agent and the polar group of the non-metallic powder of the waste printed circuit board occur condensation reaction, so that the macromolecule of the silane coupling agent is anchored on the surface of the non-metallic powder of the waste printed circuit board, to improve the surface treatment of the non-metallic powder of the waste printed circuit board and the compatibility with the waste polypropylene particles, at the same time, the amino group of the silane coupling agent and the active functional group of the chitosan powder occur crosslinking reaction, to make the chitosan powder, the silane coupling agent and the non-metallic powder of the waste printed circuit board produce a preliminary crosslinking network, so that the crosslinking network shields the polar group of the chitosan powder, reduces the surface energy of the mixed powder to be treated, and obtains the modified powder with similar surface energy to the waste polypropylene particles, to improve the interfacial compatibility, so as to regenerate and utilize the waste polypropylene plastic and the non-metallic part of the waste printed circuit board and prepare the composite material with certain mechanical properties, so as to effectively save resources, reduce costs and reduce the pollution of the above waste to the environment. BRIEF DESCRIPTION OF DRAWINGS
[0017] Figure 1 The present application provides a flow chart of a preparation method of a composite material regenerated by waste.
[0018] Figure 2 The SEM graph of the impact section of the composite material sample 1 regenerated by waste in the method embodiment 1 of the present application. DETAILED DESCRIPTION
[0019] In order to further understand the present application, the preferred embodiments of the present application are described below in combination with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present application, but not for limiting the claims of the present application.
[0020] Please refer to Figure 1 In one aspect, the present application provides a preparation method of a composite material regenerated by waste, comprising the following steps: Step 1: mixing and stirring the chitosan powder and the non-metallic powder of the waste printed circuit board according to the mass ratio of (15-20):(30-60), to obtain the mixed powder to be treated; Step 2: adding a certain amount of hydrolyzed silane coupling agent into the mixed powder to be treated at a predetermined temperature and stirring, to perform surface treatment and preliminary crosslinking on the mixed powder to be treated by the silane coupling agent, to obtain the modified powder, wherein the mass ratio of the silane coupling agent to the mixed powder to be treated is (1.4-1.6):100; Step 3: the modified powder, waste polypropylene particles and antioxidant are mixed in a mass ratio of (30-50):200:0.5, and after stirring, a composite sample powder is obtained; Step 4: the composite sample powder is extruded, granulated and injection molded to obtain a waste-regenerated composite material.
[0021] In this way, the tensile strength of the composite material prepared by the above method can reach 34.12 MPa, the bending strength can reach 35.10 MPa, and the impact strength can reach 24.34 kJ / m 2 .
[0022] The present application has the following advantages over the prior art: for the first time, chitosan powder and non-metallic powder of waste printed circuit board are compounded and modified, specifically, the silanol group of the silane coupling agent reacts with the polar group of the non-metallic powder of the waste printed circuit board to anchor the macromolecule of the silane coupling agent on the surface of the non-metallic powder of the waste printed circuit board, thereby improving the surface treatment of the non-metallic powder of the waste printed circuit board and improving the compatibility with the waste polypropylene particles, at the same time, the amino group of the silane coupling agent reacts with the active functional group of the chitosan powder to produce a preliminary crosslinking network between the chitosan powder, the silane coupling agent and the non-metallic powder of the waste printed circuit board, so that the crosslinking network shields the polar group of the chitosan powder, reduces the surface energy of the mixed powder to be treated, and obtains a modified powder with surface energy similar to that of the waste polypropylene particles, thereby improving the interfacial compatibility, so as to regenerate and utilize the waste polypropylene plastic and the non-metallic part of the waste printed circuit board and prepare a composite material with certain mechanical properties, thereby effectively saving resources, reducing costs and reducing pollution of the above waste to the environment.
[0023] In order to activate the interface modification function of the silane coupling agent (KH-550), the silane coupling agent (KH550) is mixed with water and ethanol in a volume ratio of (9-15):(6-9):(40-60), and stirred at room temperature for 20-40 min to obtain the silane coupling agent hydrolyzed in the present application.
[0024] In a preferred embodiment, the antioxidant can be one or more of antioxidant 1010, antioxidant 168, stearic acid and zinc stearate.
[0025] Further, chitin is the second most abundant natural polysaccharide in nature, mainly existing in the exoskeleton or cell wall of marine arthropods, insects and other organisms, and specifically, the chitosan powder is obtained by extracting waste crab and shrimp shells, thereby effectively preventing pollution of waste shrimp and crab shells to the living environment, and the chitosan powder is obtained by the following steps: S11: placing the waste shrimp and crab shells into a container, adding 1 mol / L-2 mol / L sodium hydroxide solution to submerge the waste shrimp and crab shells, then heating the sodium hydroxide solution to boiling for 1 h-2 h, and filtering to obtain the shrimp and crab shells to be extracted, so as to remove the proteins and fats in the waste shrimp and crab shells; S12: soaking the shrimp and crab shells to be extracted in 0.9 mol / L-1.1 mol / L hydrochloric acid at room temperature for 4 h-8 h, filtering and crushing to obtain chitin powder of a certain particle size, wherein the hydrochloric acid dissolves the inorganic substances such as calcium carbonate in the shrimp and crab shells to be extracted, so that pure chitin powder can be obtained, and the mass ratio of the hydrochloric acid to the shrimp and crab shells to be extracted is 1:(5-10), and the particle size of the chitin powder is 80-100 mesh. S13: dissolving the chitin powder in an industrial sodium hydroxide solution with a mass fraction of 40%-50% to obtain a mixed solution, wherein the mass ratio of the chitin powder to the industrial sodium hydroxide solution is (1-2):(10-20). S14: heating the mixed solution to a temperature of 60℃-80℃ for 6 h-12 h, filtering to obtain chitosan powder to be treated, so as to remove the acetyl groups of the chitin powder to obtain the chitosan powder to be treated with high deacetylation degree, and ensure that the chitosan powder can provide more active functional groups (-NH2 / -OH) as crosslinking points of the silane coupling agent, and enhance the shielding rate of the crosslinking network to the polar groups of the chitosan powder. S15: washing the chitosan powder to be treated to neutral with distilled water, and drying at a temperature of 55℃-65℃ to obtain the chitosan powder, so as to avoid the influence of the residual drug solution of the chitosan powder on the subsequent modification reaction.
[0026] Further, in step 1, the specific steps for obtaining the waste printed circuit board non-metallic powder are: crushing the non-metallic part of the waste printed circuit board, and then sieving to obtain the waste printed circuit board non-metallic powder with a particle size of 80-100 mesh, so that the waste printed circuit board non-metallic powder has a suitable specific surface area, which can ensure sufficient contact with the chitosan powder and the silane coupling agent, and avoid agglomeration of the powder to affect the subsequent modification of the silane coupling agent.
[0027] Further, step 1 is specifically: placing the chitosan powder and the waste printed circuit board non-metallic powder into a high-speed mixer for stirring to obtain the mixed powder to be treated, wherein the mass ratio of the chitosan powder to the waste printed circuit board non-metallic powder is (15-20):(30-60).
[0028] Further, the step 2 is specifically: after the temperature in the high-speed mixer rises to the predetermined temperature, a certain amount of hydrolyzed silane coupling agent is added into the mixed powder to be treated in multiple times and continuously stirred for 15-25 min, so as to perform surface treatment and preliminary cross-linking on the mixed powder to be treated by the silane coupling agent, and modified powder is obtained, wherein the predetermined temperature is 75-85℃, and the mass ratio of the silane coupling agent to the mixed powder to be treated is (1.4-1.6):100.
[0029] Further, the step 2 further includes a drying step after being completed, and the drying step is specifically: the modified powder is placed in an electric heating constant temperature drying box and dried at 75-85℃ for 2.5-3.5h, so as to remove excess moisture.
[0030] Further, maleic anhydride grafted polypropylene is added in the step 3 as a compatibilizer of the composite sample powder, and the mass ratio of the modified powder, the waste polypropylene powder, the antioxidant and the maleic anhydride grafted polypropylene is (30-50):200:0.5:(6-9), the maleic anhydride functional groups in the molecular chain of the maleic anhydride grafted polypropylene will chemically react with the hydroxyl or amino groups of the modified powder or form strong hydrogen bonds, and the polypropylene segments of the maleic anhydride grafted polypropylene and the molecular chains of the waste polypropylene powder will be intertwined together, so as to ensure that the modified powder and the waste polypropylene powder form a firm interfacial bonding, so as to improve the mechanical properties of the composite material regenerated by waste.
[0031] Further, in order to prevent the molecular chain of the waste polypropylene from being easily broken due to aging degradation, OBC elastomer is added in the step 3 as a toughening agent of the composite sample powder, and the mass ratio of the modified powder, the waste polypropylene powder, the antioxidant and the OBC elastomer is (30-50):100:0.5:(9-15).
[0032] Further, the step 3 also adds a β nucleating agent as an induced nucleating agent of the composite sample powder, wherein the mass ratio of the modified powder, the waste polypropylene powder, the antioxidant and the β nucleating agent is (30-50):100:0.5:(1-2), and in the present application, the β nucleating agent can be specifically WBG-II polypropylene β nucleating agent. The polypropylene in the composite sample powder is induced by the WBG-II polypropylene β nucleating agent to generate a large amount of β crystals (the β crystal content can reach 60-80%) when cooled, and the lamellar arrangement is more loose. The impact energy can be absorbed through "micro-fibrillation" and "cavitation", which can significantly improve the toughness of the waste polypropylene matrix and delay crack propagation. At the same time, due to the plastic deformation ability of β crystals is better than that of α crystals, it can hinder the crack propagation in the polypropylene phase, optimize the interfacial compatibility of polypropylene and epoxy resin, the (300) crystal face of β crystal contains more exposed methyl groups, which can form weak interaction with the polar groups (such as hydroxyl and epoxy groups) of epoxy resin through van der Waals force, improve the interfacial adhesion, and the toughness deformation ability of β crystal makes the polypropylene and epoxy resin interface more uniform in stress dispersion, reduces the interfacial debonding, and can delay the deformation of the composite material regenerated from waste under thermal load, thereby improving the mechanical properties.
[0033] In another aspect, the present application provides a composite material regenerated from waste, which is prepared by the method for preparing a composite material regenerated from waste according to the previous aspect.
[0034] The technical scheme and technical effects of the present application are further illustrated by the following examples and comparative examples of the method of the present application. It should be noted that the following experimental examples are only for further explaining the present application and do not limit the technical scheme of the present application.
[0035] Example 1: The waste shrimp and crab shells washed with clean water to remove silt were placed in a container, and 1.5 mol / L sodium hydroxide solution was added to submerge the waste shrimp and crab shells. Then the sodium hydroxide solution was heated and boiled for 2 h, and then filtered to obtain the extracted shrimp and crab shells. The extracted shrimp and crab shells were soaked in 1 mol / L hydrochloric acid at room temperature for 6 h, then filtered and crushed to obtain chitin powder with a certain particle size. The mass ratio of hydrochloric acid to extracted shrimp and crab shells was 1:8, and the particle size of chitin powder was 90 mesh. The chitin powder was dissolved in an industrial sodium hydroxide solution with a mass fraction of 45% to obtain a mixed solution. The mass ratio of chitin powder to industrial sodium hydroxide solution was 1:10. The treated chitin powder was washed to neutral with distilled water and dried at 60°C to obtain chitin powder. The non-metallic part of the waste printed circuit board was crushed and then sieved to obtain 90 mesh waste printed circuit board non-metallic powder. The chitosan powder and the non-metallic powder of the waste printed circuit board are put into a high-speed mixer for sufficient stirring to obtain a mixed powder to be treated, wherein the mass ratio of the chitosan powder to the non-metallic powder of the waste printed circuit board is 18:40; After the temperature in the high-speed mixer is raised to 80℃, the hydrolyzed silane coupling agent is added dropwise into the mixed powder to be treated in multiple times and stirring is continuously performed for 20 min to perform surface treatment and preliminary crosslinking on the mixed powder to be treated by the silane coupling agent, and the mass ratio of the silane coupling agent to the mixed powder to be treated is 1.5:100; The modified powder is put into an electric heating constant temperature drying oven and dried at 80℃ for 3 h, and the modified powder, the waste polypropylene particles and the antioxidant are put into a high-speed mixer at a temperature of 40℃ and mixed and stirred sufficiently for 15 min at a mass ratio of 40:200:0.5 to obtain a composite sample powder; The composite sample powder is extruded into a strip shape by a twin-screw extruder, and granulation is performed by using a granulator, and the process parameters of the twin-screw extruder are as follows: the temperature of the first section is 180℃, the temperature of the second section is 195℃, the temperature of the third section is 200℃, the temperature of the fourth section is 190℃, the die head temperature is 180℃, the melt temperature is 185℃, the screw rotation speed is 140 r·min-1, and the feeding rotation speed is 12 r·min-1, and then the composite particles are put into an electric heating constant temperature drying oven and dried at 80℃ for 6 hours; The dried composite particles are added into an injection molding machine for molding to obtain a composite material sample 1 regenerated from waste, and the process parameters of the injection molding machine are as follows: the nozzle temperature is 210℃, the temperature of the first section is 205℃, the temperature of the second section is 195℃, the temperature of the third section is 180℃, the holding pressure is 60 MPa, and the cooling time is 25 seconds.
[0036] Example 2: Compared with Example 1, maleic anhydride grafted polypropylene is further added to the composite sample powder, wherein the mass ratio of the modified powder, the waste polypropylene powder, the antioxidant and the maleic anhydride grafted polypropylene is 40:200:0.5:7, and other conditions are the same as those in Example 1, to obtain a composite material sample 2 regenerated from waste.
[0037] Example 3: Compared with Example 2, OBC elastomer is further added to the composite sample powder, wherein the mass ratio of the modified powder, the waste polypropylene powder, the antioxidant and the OBC elastomer is 40:200:0.5:7:12, and other conditions are the same as those in Example 1, to obtain a composite material sample 3 regenerated from waste.
[0038] Example 4: Compared with Example 3, WBG-II polypropylene β nucleating agent was also added in the composite sample powder, wherein the mass ratio of modified powder, waste polypropylene powder, antioxidant and WBG-II polypropylene β nucleating agent was 40:200:0.5:7:12:2, and other conditions were the same as those in Example 1, to obtain a composite material sample 4 regenerated by waste.
[0039] Example 5: Compared with Example 4, flame retardant decabromodiphenyl ether was also added in the composite sample powder, wherein the mass ratio of modified powder, waste polypropylene powder, antioxidant, WBG-II polypropylene β nucleating agent and decabromodiphenyl ether was 40:200:0.5:7:12:2:0.5, and other conditions were the same as those in Example 1, to obtain a composite material sample 5 regenerated by waste.
[0040] Comparative Example: Compared with Example 1, only waste printed circuit board non-metallic powder, waste polypropylene particles and antioxidant were contained in the composite sample powder, wherein the mass ratio of waste printed circuit board non-metallic powder, waste polypropylene particles and antioxidant was 40:200:0.5, and other conditions were the same as those in Example 1, to obtain a composite material sample 6 regenerated by waste.
[0041] In the above Examples 1 to 5 and Comparative Example, the mechanical properties of the composite material samples regenerated by waste were tested, the tensile and bending properties were tested according to GB / T1040-1992 and GB / T9341-2000 standards respectively, using a universal testing machine, the test speed was 10 mm / min and 2 mm / min respectively, 5 samples were tested in each group and the test average value was taken, the impact property was tested according to GB / T1843-1996 standard, using a cantilever beam impact testing machine, a 1J pendulum was selected, 10 samples were tested in each group and the test average value was taken, and the specific test results are shown below: Table of mechanical property test results
[0042] It can be seen that, through the mechanical property test, the tensile strength of the composite material sample regenerated by waste in Example 1 was 34.12 MPa, the bending strength was 35.10 MPa, and the impact strength was 24.34 kJ / m 2 , which reached the national mechanical property execution standard (CJ / T212-2005) of manhole cover and grating, and the mechanical properties gradually increased with the addition of maleic anhydride grafted polypropylene, OBC elastomer and WBG-II polypropylene β nucleating agent, and the limiting oxygen index of the sample in Example 5 could reach 25.6 close to difficult combustion after adding flame retardant decabromodiphenyl ether.
[0043] In order to further verify the mechanical properties of the composite material sample regenerated by waste, please refer toFigure 2 The SEM image of the impact fracture of the composite sample 1 regenerated by waste in Example 1 can clearly see the phenomenon of fiber fracture, interface roughness, which proves that the interface compatibility of glass fiber, epoxy resin and polypropylene in the non-metallic powder of the waste printed circuit board is high, so that the mechanical property is better.
[0044] The above only discloses the preferred embodiments of the present application, of course, cannot be limited by this to limit the scope of the present application, those skilled in the art can understand that the whole or part of the above-mentioned embodiments are implemented, and the equivalent changes made according to the claims of the present application still belong to the scope covered by the present application.
Claims
1. A method for preparing a composite material using recycled waste, characterized in that, Includes the following steps: Step 1: Mix chitosan powder and waste printed circuit board non-metallic powder in a mass ratio of (15-20):(30-60) and stir to obtain the mixed powder to be processed; Step 2: At a predetermined temperature, a certain amount of hydrolyzed silane coupling agent is added to the mixed powder to be treated and stirred to perform surface treatment and preliminary crosslinking on the mixed powder to be treated by the silane coupling agent, thereby obtaining modified powder, wherein the mass ratio of the silane coupling agent to the mixed powder to be treated is (1.4-1.6):
100. Step 3: Mix the modified powder, waste polypropylene granules and antioxidant in a mass ratio of (30-50):200:0.5 and stir to obtain composite sample powder; Step 4: Extrude and granulate the composite sample powder and injection mold it to produce a composite material made from recycled waste.
2. The method for preparing composite materials from recycled waste according to claim 1, characterized in that, In step 1, the chitosan powder is obtained through the following steps: S11: Place the waste shrimp and crab shells in a container and add 1 mol / L-2 mol / L sodium hydroxide solution to submerge the waste shrimp and crab shells. Then heat the sodium hydroxide solution to boil for 1-2 hours and filter to obtain the shrimp and crab shells to be extracted. S12: Soak the shrimp and crab shells to be extracted in 0.9mol / L-1.1mol / L hydrochloric acid at room temperature for 4-8 hours, then filter and pulverize to obtain chitin powder of a certain particle size, wherein the mass ratio of hydrochloric acid to the shrimp and crab shells to be extracted is 1:(5-10), and the particle size of the chitin powder is 80-100 mesh. S13: Dissolve the chitin powder in an industrial sodium hydroxide solution with a mass fraction of 40%-50% to obtain a mixed solution, wherein the mass ratio of the chitin powder to the industrial sodium hydroxide solution is (1-2):(10-20). S14: The mixed solution is heated to 60℃-80℃ and reacted for 6h-12h, then filtered to obtain the chitosan powder to be treated; S15: Rinse the chitosan powder to be treated with distilled water until neutral, and then dry it at a temperature of 55℃-65℃ to obtain the chitosan powder.
3. The method for preparing composite materials from recycled waste according to claim 1, characterized in that, In step 1, the specific steps for obtaining the non-metallic powder from the waste printed circuit board are as follows: the non-metallic part of the waste printed circuit board is crushed and then sieved to obtain the non-metallic powder from the waste printed circuit board with a particle size of 80-100 mesh.
4. The method for preparing composite materials from recycled waste according to claim 1, characterized in that, Step 1 specifically involves: placing the chitosan powder and the waste printed circuit board non-metallic powder into a high-speed mixer and stirring them to obtain a mixed powder to be processed, wherein the mass ratio of the chitosan powder to the waste printed circuit board non-metallic powder is (15-20):(30-60).
5. The method for preparing composite materials from recycled waste according to claim 4, characterized in that, Step 2 specifically involves: after the temperature inside the high-speed mixer reaches the predetermined temperature, adding a certain amount of hydrolyzed silane coupling agent dropwise into the mixed powder to be treated in multiple batches and stirring continuously for 15-25 minutes, so as to perform surface treatment and preliminary crosslinking on the mixed powder to be treated by the silane coupling agent to obtain modified powder. The predetermined temperature is 75℃-85℃, and the mass ratio of the silane coupling agent to the mixed powder to be treated is (1.4-1.6):
100.
6. The method for preparing composite materials from recycled waste according to claim 1, characterized in that, After step 2 is completed, a drying step is also included. The drying step specifically involves placing the modified powder in an electric thermostatic drying oven and drying it at 75℃-85℃ for 2.5-3.5 hours to remove excess moisture.
7. The method for preparing composite materials from recycled waste according to claim 1, characterized in that, In step 3, maleic anhydride-grafted polypropylene is added as a compatibilizer for the composite sample powder, wherein the mass ratio of the modified powder, the waste polypropylene powder, the antioxidant, and the maleic anhydride-grafted polypropylene is (30-50): 200: 0.5: (6-9).
8. The method for preparing composite materials from recycled waste according to claim 1, characterized in that, In step 3, OBC elastomer is added as a toughening agent for the composite sample powder, wherein the mass ratio of the modified powder, the waste polypropylene powder, the antioxidant and the OBC elastomer is (30-50):100:0.5:(9-15).
9. The method for preparing composite materials from recycled waste according to claim 1, characterized in that, In step 3, a β-nucleating agent is added as an inducing nucleating agent for the composite sample powder, wherein the mass ratio of the modified powder, the waste polypropylene powder, the antioxidant, and the β-nucleating agent is (30-50):100:0.5:(1-2).
10. A composite material utilizing recycled waste, characterized in that, It is prepared by the method for preparing composite materials using waste recycling as described in any one of claims 1-9.
